Perencanaan Kerja Sama Lembaga Pendidikan Islam - Syarifuddin Mukhtar, Amir; Endin Mujahidin; Nesia Andriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the significance of planning and collaboration in enhancing the effectiveness of Islamic educational institutions. Systematic and effective planning serves as a critical element in achieving educational goals. Collaboration principles rooted in Islamic values, such as ta'awun (mutual assistance in goodness), play a vital role in fostering synergy among educational institutions, communities, governments, and private sectors. Identified challenges include lack of coordination, limited resources, and sustainable commitment, which can be addressed through visionary leadership, active parental involvement, and external support. This study emphasizes that collaborative and well-planned approaches can improve the quality of Islamic education and support the achievement of collective welfare.